KAPASITAS LAPANG DAN PERTUMBUHAN CABAI MERAH KERITING (Capsicum annum L.) PADA JENIS DAN PEMBENAH TANAH YANG BERBEDA - Novi Sultonia Farida; Sri Widodo Agung Suedy; Endah Dwi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Clay and sandy soil are critical area that have been damaged due to the very low rainfall or poor soil texture and in result recuding the function of water and soil. Such soils can be restored by using repairing soil materials tahat can improve soil structure by affeeting the soil field capacity and pull through the water. In result, it can support the growth of plant. The addition of repairing soil can increase field capacity and the growth of curly red chili. This study aims to determine the effect of repairing soil, soil types (clay and sandy) and the interaction between soil types and repairing soil soil that affecting field capacity and the growth of curly red chili. The research was conducted in Ringinarum village, Kendal, and plant BSF Laboratory, FSM Undip. The research design was a Completely Randomized Design (CRD) with a 2x3 factorial pattern, each treatmentnhad 3 repetitions. The firs factor was soil (T): Sandy (P) and Clay (L), while the second factor: S0 (control/without repairing soil), S1 (rice husk repairing soil) and S2 (rice straw repairing soil). Analysis of the data was using Analysis of Variance (ANOVA) followed by Duncan’s Test significant difference of Multiple Range Test (DMRT) at the 95% significance level. The observed parameters were field capacity, plant height, number of leaves, fresh weight and dry weight of chilies. The results showed that the addition of repairing soil affected the field capacity and the growth of curly red chili. Field capacity of control (without repairing soil) of 17,3%, rice husk repairing soil of 66,76%, and rice straw repairing soil of 80,51% (increased). The addition of repairing soil of rice straw was more optimal that rice husk and soil without repairing soil. The plant was better growth on clay than on sandy soil. Keywords : sandy soil and clay soil, repairing soil, field capacity, rice husk, rice straw